The Suitability of Using C30E Steel Materials for Damping the Effects of Improvised Explosive Devices - Norbert ADAMEC (Wojskowa Akademia Techniczna, 2012)
There are nowadays different kinds of homogenous steel armours (e.g. different kinds of steel sheets Armox, Russian armours including 2P, 43 PSM etc.) or aramide fibres which can be used alone or in composites. This paper follows the relationship between the strength parameters and microstructure in the steel armours used for personal protection and military vehicles. The results described in the paper, pick up the threads of previous work performed at the Mechanical Engineering Department in Armed Forces Academy of gen. M.R. Stefanik in Liptovsky Mikulas.
Keywords: Stal pancerna do ochrony osobistej i wozów bojowych